2D:4D Ratio in Neurodevelopmental Disorders: A Twin Study - Myers, L.; van t Westeinde, A.; Kuja-Halkola, R.; Tammimies, K.; Bolte, Sven (Springer New York LLC, 2018)
The second to fourth digit (2D:4D) ratio is of interest in autism spectrum disorder (ASD). Studies on the relationship of this ratio with other neurodevelopmental disorders (NDDs) are lacking. Investigating the association between the ratio and NDDs in twins can provide insight into genetic and/or environmental factors driving the ratio. Hand images were collected in N = 238 twins with NDDs or typical development from 70 monozygotic and 49 dizygotic pairs to examine ratios and their associations to DSM-5 defined categorical NDDs, autistic traits, zygosity, and sex. There were small associations for males between the ratios and any NDD and ADHD diagnoses. Males had lower ratios than females. Future studies exploring the ratio alongside physical anomalies could provide etiological insight into NDDs.